Culturally capable and culturally safe: Caseload care for Indigenous women by Indigenous midwifery students. Issue 6 (December 2016) - West, R.; Gamble, J.; Kelly, J.; Milne, T.; Duffy, E.; Sidebotham, M.
Abstract: Background: Evidence is emerging of the benefits to students of providing continuity of midwifery care as a learning strategy in midwifery education, however little is known about the value of this strategy for midwifery students. Aim: To explore Indigenous students' perceptions of providing continuity of midwifery care to Indigenous women whilst undertaking a Bachelor of Midwifery. Methods: Indigenous Bachelor of Midwifery students' experiences of providing continuity of midwifery care to Indigenous childbearing women were explored within an Indigenous research approach using a narrative inquiry framework. Participants were three Indigenous midwifery students who provided continuity of care to Indigenous women. Findings: Three interconnected themes; facilitating connection, being connected, and journeying with the woman . These themes contribute to the overarching finding that the experience of providing continuity of care for Indigenous women creates a sense of personal affirmation, purpose and a validation of cultural identity in Indigenous students. Discussion and conclusions: Midwifery philosophy aligns strongly with the Indigenous health philosophy and this provides a learning platform for Indigenous student midwives. Privileging Indigenous culture within midwifery education programs assists students develop a sense of purpose and affirms them in their emerging professional role and within their community. The findings from this study illustrate the demand for, and pertinence of, continuity of care midwifery experiences with Indigenous women as fundamental to increasing the Indigenous midwifery workforce in Australia. Australian universities should provide this experience for Indigenous student midwives.